Pengembangan Organisasi pada Sistem Administrasi Manunggal Satu Atap (SAMSAT) Provinsi Kepulauan Riau - Maulana, Irfan (Jurnal Ilmu Administrasi Negara (JUAN), 2014)
Research development organization SAMSAT Riau Islands Province alignment within the organizationis measured by using a model of congruence of Nadler - Tushman. From this model gained fourdimensions, namely, input, output, process transformation and congruence. With four dimensions inthis model explains 27buah indikators that can be measured to see the process of organizational developmentSAMSAT Riau Islands Province. Indikator is obtained through questionnaires in the fieldwhich is then processed using a simple interval class. Having analyzed the overall indikator didapatkanlahfinal interval value which is equal to 4.17. The results of this statistical analysis melmilikiSAMSAT meaning that development organizations are categorized either because the process inputs(input), the output (output), a process that occurs within the organization tarnsformasi occur in harmonyor balance which leads to increased efficiency and effectiveness of the organization SAMSAT, besidesthat it can improve progress of the organization to make it more alive. With the development ofboth the organization acquired symptoms - symptoms that are found at the beginning of the study canbe addressed by the organization SAMSAT. So for the future is expected to SAMSAT organization canimprove its organizational development, so as to achieve effectiveness and efficiency in the organizationas expected.